Microbial Polyethylene Terephthalate Hydrolases: Current and Future Perspectives - Carr, Clodagh M.; Clarke, David J.; Dobson, Alan D. W. (Frontiers in Microbiology, 2020)
Since gaining popularity over 50 years ago, plastic has transformed our world, with many aspects of modern life relying on plastic materials. However, the qualities which have made plastic an attractive resource, such as ease of mass production and advantageous strength-to-weight ratio, are equally as responsible for the damage that is typically caused once it becomes waste. In recent years, biological plastic degradation has emerged as one way to address these unforeseen consequences. This strategy involves using microorganisms, primarily bacteria and fungi, which have enzymes capable of catalyzing degradative reactions, to break plastic apart into its original components. The focus of this review will be on microbial hydrolase enzymes found to act on polyethylene terephthalate or PET plastic, that is widely found as packaging and synthetic fibers among other forms. The best characterized examples will be discussed along with the use of metagenomic and protein engineering technologies in obtaining PET hydrolase enzymes for application. In addition, the obstacles which are currently limiting the development of efficient PET bioprocesses will be presented. By continuing to study the possible mechanisms and key enzyme structural elements behind microbial PET hydrolysis and assessing the ability of PET hydrolase enzymes under practical conditions, this research can progress towards use in large-scale waste management operations. Finally, the contribution of microbial PET hydrolases in creating a circular PET economy will be explored